Post Graduate Business Education: Tracing through Different Learning Methods in Controversial Subjects Teaching - Meena J. Panikker, Dr.; Muhamad Shafi, Dr. (International Journal of Engineering and Technology, 2018)
â€˜Business, Government and Societyâ€™ is one of the subjects for the Management curriculum at most of the B-Schools and the National Institute of Technology Calicut is also one such. The subject includes two components - business and government, and business and society; the teaching of this subject involves great challenges primarily due to the nature of the subject itself and also because of the diversity of the student group. The subject predominantly deals with:a) How the society influences the ethics of business.b) How the strategies of the government are linked with business.These issues need to be highlighted because India is a pluralistic society and hence the great variation in the degree of the awareness of the issues under discussion within the scope of this subject as well as the huge dissimilarity in their level of acceptance of certain elements pertaining to these issues, especially so, because they belong to the different communities. The students for the Management programme at the National Institute of Technology Calicut come from various communities across India. This study explores how the students respond to the different methods of learning namely, conventional learning, collaborative learning, and cooperative learning and also analyses which of these methods promote a healthy cognitivism in the students. The study was conducted among ten students (five from Kerala and five from non-Kerala) across five different batches over the years, 2012-2017. It was noted that through conventional learning there was hardly any change in the studentsâ€™ personal ideologies which were often in conflict with the ideologies of the other students.Â It was also noted that it was through collaborative and cooperative learning methods that the students were able to diffuse their personal political ideologies in the larger interests of the state. It was also noted that through the method of cooperative learning for the teaching of this subject, that the cognitive development in the students was encouraged. The relevance of including such a subject in the curriculum was thus established and the goals of teaching the subject were also fulfilled because it helped in creating better student awareness and also traced a better way for the students to arrive at solutions for the problems concerned.Â Â